Hinokitiol induces cell death and inhibits epidermal growth factor-induced cell migration and signaling pathways in human cervical adenocarcinoma - Chih-Chun Wang; Ben-Kuen Chen; Peng-Hsu Chen; Lei-Chin Chen (Elsevier, 2020)
Objective: The aim of this study was to examine the antitumor activity of hinokitiol for its clinical application in the treatment of human cervical carcinoma. Materials and methods: Cervical carcinoma HeLa cells were treated by different concentrations of hinokitiol. Flow cytometry was used to analyze cell cycle. Senescence-associated β-galactosidase (SA-β-gal) assay was used to identify senescent cells. The effects of hinokitiol on EGF-induced cell migration were determined by wound healing and transwell migration assays. Western blot was used to detect proteins involved in cell cycle progression, apoptosis, autophagy, and EGF-induced signaling pathways. Results: Hinokitiol suppressed cell viability in a dose-dependent manner. Flow cytometric analysis indicated that hinokitiol treatment resulted in cell cycle arrest at G1 phase, with reduced number of cells in the G2/M phase. Western blot analysis further demonstrated that hinokitiol treatment increased the levels of p53 and p21, and concomitantly reduced the expression of cell cycle regulatory proteins, including cyclin D and cyclin E. SA-β-gal assay showed that hinokitiol treatment significantly induced β-galactosidase activity. In addition, treatment with hinokitiol increased the accumulation of the autophagy regulators, beclin 1 and microtubule-associated protein 1 light chain 3 (LC3-II), in a dose-dependent manner; however, it did not induce caspase-3 activation and poly ADP ribose polymerase (PARP) cleavage. In addition, epidermal growth factor-induced cell migration and c-Jun N-terminal kinase (JNK) and focal adhesion kinase (FAK) phosphorylation were significantly inhibited by hinokitiol. Conclusion: Our findings revealed that hinokitiol might serve as a potential therapeutic agent for cervical carcinoma therapy.